2008
DOI: 10.1152/ajpheart.00629.2008
|View full text |Cite
|
Sign up to set email alerts
|

Internalization of eNOS via caveolae regulates PAF-induced inflammatory hyperpermeability to macromolecules

Abstract: Endothelial nitric oxide (NO) synthase (eNOS) is thought to regulate microvascular permeability via NO production. We tested the hypotheses that the expression of eNOS and eNOS endocytosis by caveolae are fundamental for appropriate signaling mechanisms in inflammatory endothelial permeability to macromolecules. We used bovine coronary postcapillary venular endothelial cells (CVECs) because these cells are derived from the microvascular segment responsible for the transport of macromolecules in inflammation. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
62
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(67 citation statements)
references
References 36 publications
4
62
1
Order By: Relevance
“…5B shows a series of images demonstrating that: (i) PAF and VEGF induce translocation of eNOS from the plasma membrane (caveolae) to the cytosol in postcapillary ECs; and (ii) transfection of ECs with cav1Y14F inhibits the translocation of eNOS. Translocation of eNOS is indicated mainly by the disappearance of eNOS from the cell plasma membrane and the enhanced brightness in the cytosol (6,7).…”
Section: Inhibition Of Enos Endocytosis Inhibits Vegf-induced Hyperpementioning
confidence: 99%
See 4 more Smart Citations
“…5B shows a series of images demonstrating that: (i) PAF and VEGF induce translocation of eNOS from the plasma membrane (caveolae) to the cytosol in postcapillary ECs; and (ii) transfection of ECs with cav1Y14F inhibits the translocation of eNOS. Translocation of eNOS is indicated mainly by the disappearance of eNOS from the cell plasma membrane and the enhanced brightness in the cytosol (6,7).…”
Section: Inhibition Of Enos Endocytosis Inhibits Vegf-induced Hyperpementioning
confidence: 99%
“…We previously showed that eNOS internalization (endocytosis) is a required step in the signaling cascade leading to PAF-induced hyperpermeability (7). In this study, we tested the hypothesis that caveolar internalization of eNOS is a requirement for localized NO production and NO delivery to a subcellular target to cause hyperpermeability.…”
mentioning
confidence: 94%
See 3 more Smart Citations